Determination of antibiotic residues in southern Baltic Sea sediments using tandem solid-phase extraction and liquid chromatography coupled with tandem mass spectrometry - Grzegorz Siedlewicz; Marta Borecka; Anna Białk-Bielińska; Kinga Sikora; Piotr Stepnowski; Ksenia Pazdro (Oceanologia, 2016)
The main objective of this study was to adapt analytical procedures for determining antibiotic residues in solid and aquatic samples to marine sediments and to investigate the occurrence of 9 sulfonamides, trimethoprim and 2 quinolones in southern Baltic Sea sediments. The analytical procedure was applied to sediment samples characterized as sand and silty sand. The validation results showed that a sensitive and efficient method applying tandem solid-phase extraction (SPE) and liquid chromatography coupled with tandem mass spectrometry (LC–MS/MS) was obtained. Analytes were determined in the lower ng g−1 range with good accuracy and precision. The proposed analytical procedure was applied to the analysis of 13 sediment samples collected from the Baltic Sea along the Polish coast. Concentrations of antibiotic residues in environmental samples were calculated based on external matrix-matched calibration. Residues of nine out of twelve of the above antibiotics were detected in sediment samples in a concentrations of up to 419.2 ng g−1 d.w. (dry weight). Sulfamethoxazole and sulfachloropyridazine were the most frequently detected compounds (58% of the analyzed samples). The occurrence frequency of trimethoprim was 42% and it was always detected simultaneously with sulfamethoxazole. Preliminary studies on the spatial distribution of the analyzed antibiotics indicate a high level of antibiotics occurring in the Pomeranian Bay and close to the mouths of Polish rivers. The study is the first one to demonstrate the occurrence of antibiotic residues in sediments of the Polish coastal area. The obtained results suggest that sediment can be an important secondary source of antibiotic residues in the marine environment.